Left ventricular postoperative false aneurysm following apical venting - Muzzi Luigi; Frati Giacomo; Rose David; Bizzarri Federico (Journal of Cardiothoracic Surgery, 2006)
Abstract We report a case of false aneurysm of the left ventricle occurring subsequently to the placing of a vent sump line through the apex during an aortic valve procedure; the diagnosis was made twelve months later during a routine echocardiographic examination. The lesion was successfully repaired. This case recommend the use of other routes of venting in order to reduce the incidence of such complications.